Сверхскоростное затачивание твёрдосплавного инструмента; СТИН. СТанки ИНструмент; № 4 - Реченко Д. С. Денис Сергеевич; Попов А. Ю. Андрей Юрьевич; Бабаев А. С. Артём Сергеевич; Лаптев Н. В. Никита Витальевич (2018, 2018)
Заглавие с экрана